Non-bacterial Thrombotic Endocarditis in Lung Cancer: A Systematic Review - Kamel, Maikel; Hussain, Fahad; Leung, Christian; Paracha, Awais; Sathe, Pranav; Jassal, Ajay; Huba, Mahalia; Durrani, Umar; Ammari, Nadim; Copeland-Halperin, Robert S.; Seetharamu, Nagashree (Current Cardiology Reviews, 2025)
IntroductionNon-bacterial Thrombotic Endocarditis (NBTE) is a rare condition characterized by aseptic vegetations of the heart valves, predisposing to valvular dysfunction and end-organ infarction. Lung Cancer (LC) is amongst the most common malignancies associated with NBTE.MethodsPubMed/MEDLINE was searched from database inception until January 2024, pairing Non-bacterial Thrombotic Endocarditis (NBTE) and related terms with “Lung Cancer (LC)”. Reports were included if patients had both NBTE and lung cancer. The risk of bias was assessed using Mixed Methods Analysis Testing (MMAT).Results and Discussion32 patients with an average age of 59y +/- 11.6 were included from 31 peer-reviewed publications, with significant findings as below:• The majority (47%) of patients were admitted with stroke.• The most commonly affected valve was aortic (51%), followed by mitral (43%), and tricuspid (5%).• At diagnosis of NBTE, 86% of patients had stage IV cancer.• Multi-organ infarct was common (61%), with the brain most often affected (40%).• Treatment of NBTE included antibiotics (86%), anticoagulation (50%), and cardiac surgery (6%).• Treatment of LC included traditional chemotherapy (30.7%), radiation (16%), tyrosine kinase inhibitors (11.5%), lobectomy (6%), and immunotherapy (3.8%).• Overall mortality rate was 77%.• Mortality rate was 38% in patients treated with chemotherapy and 91% in patients who did not receive chemotherapy.• Mortality rate stratified by anticoagulant: unfractionated heparin (85.7%), DOAC (75%), and LMWH (20%).ConclusionHigh clinical suspicion for NBTE in patients presenting with LC and thromboembolic phenomena can lead to changes in treatment and improved clinical outcomes.
Keywords: anticoagulation